User Satisfaction in Jak Lingko Mikrotrans Operations - Widsri Lai Lai Palamba; Hera Widyastuti (Institut Teknologi Sepuluh Nopember (ITS), 2024)
Mikrotrans is a means of transit that supports Transjakarta buses and serves residential neighbourhoods. However, travellers have lodged several concerns about the mikrotrans service's facilities and infrastructure. These concerns include drivers failing to stop at bus stops, drivers driving at excessive speeds, facility damage, inconvenient passenger wait periods, and a lack of bus arrival information. Aside from that, the bus stop lacks operational information, the bus stop pole is damaged, and the distance between bus stops varies. Using the customer satisfaction index approach and IPA-Kano integration, this study examines the operational performance of the Jak Lingko mikrotrans in terms of user satisfaction. The research findings revealed a 71,61% user satisfaction index in the satisfied group. However, all assessment attributes have negative gap values, resulting in a satisfaction score that fails to match user expectations. Based on the IPA-Kano integration analysis, three fatal category qualities were identified as high priority for service improvement. The fatal category attribute is that the driver drives the vehicle if the passenger is seated and/or both of the passenger's feet have touched the ground (A7), the vehicle's stopping time is adjusted to coincide with the completion of the passenger boarding and alighting process (A14), and there is signage, route information boards, the bus name, and the bus stop number (A22).